2020
DOI: 10.3390/biom10111530
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Methyl Caffeate against Hydrogen Peroxide-Induced Cell Damage: Involvement of Caspase 3 and Cathepsin D Inhibition

Abstract: Finding effective neuroprotective strategies to combat various neurodegenerative disorders still remain a clinically unmet need. Methyl caffeate (MC), a naturally occurring ester of caffeic acid, possesses antioxidant and anti-inflammatory activities; however, its role in neuroprotection is less investigated. In order to better characterize neuroprotective properties of MC, we tested its effectiveness in various models of neuronal cell injury in human neuroblastoma SH-SY5Y cells and in mouse primary neuronal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 64 publications
(158 reference statements)
3
28
0
Order By: Relevance
“…Interestingly, 0.7% ethanol did not change the extent of cell damage induced by the pro-apoptotic factor doxorubicin (Dox) ( Figure 4 c). Moreover, we confirmed the previous findings that the cell damage induced by H 2 O 2 or 6-OHDA in SH-SY5Y cells is oxidative stress-dependent [ 24 , 25 ] since the co-treatment with antioxidant (NAC) completely prevented the cell death evoked by these factors ( Figure 4 a,b).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Interestingly, 0.7% ethanol did not change the extent of cell damage induced by the pro-apoptotic factor doxorubicin (Dox) ( Figure 4 c). Moreover, we confirmed the previous findings that the cell damage induced by H 2 O 2 or 6-OHDA in SH-SY5Y cells is oxidative stress-dependent [ 24 , 25 ] since the co-treatment with antioxidant (NAC) completely prevented the cell death evoked by these factors ( Figure 4 a,b).…”
Section: Resultssupporting
confidence: 91%
“…Since our previous studies proved an involvement of caspase-3 and cathepsin D activation in the model of H 2 O 2 -evoked cell damage in SH-SY5Y cells [ 24 , 25 , 26 ], we examined whether or not the studied flavonols could affect these enzyme activities. IQ (50 µM), Krg (50 µM) and aRh (10 µM), when given alone, did not affect caspase-3 activity in UN- and RA-SH-SY5Y cells after 9 and 18 h of treatment, respectively ( Figure 6 a,b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, methyl caffeate ( 6 ) has a better effect than its free acid form, caffeic acid ( 5 ). Several studies on the biological activities of methyl caffeate ( 6 ) have reported its neuroprotective [ 36 ], anticancer [ 37 ], antioxidant [ 38 ], and anti-inflammatory effects [ 39 ] as well as antimicrobial and antimycobacterial activities [ 40 ]. Additionally, the induction of pancreatic islet β-cell regeneration by methyl caffeate ( 6 ) has also become clear [ 21 ], as its oral administration improved glucose tolerance in rats.…”
Section: Discussionmentioning
confidence: 99%